Family Support and Loneliness in The Elderly: Their Influence on Quality of Life - Dewi, Claudia Fariday; Marlina, Yolanta Freesneti; Dafiq, Nur (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Loneliness significantly affects the quality of life among older adults. Family support plays a crucial role as a protective factor in maintaining the health and well-being of the elderly. Positive family support is recognized as one of the key determinants in enhancing the quality of life of older individuals. This study aims to analyze the relationship between family support and the quality of life in elderly individuals experiencing loneliness. A quantitative approach was used, employing a correlational design with a cross-sectional method. A total of 80 elderly respondents were selected using purposive sampling. Data were collected using the UCLA Loneliness Scale, the Family Support Questionnaire, and the WHOQOL-BREF questionnaire. The results showed that 70.0% of the elderly respondents received adequate family support, and 80.0% had a moderate level of quality of life. Family support was found to have a significant influence on the quality of life among elderly individuals who experience loneliness. It is recommended that families provide consistent care and support to their elderly members, enabling them to feel accompanied and valued in their later years, thereby improving their overall well-being.